1979
DOI: 10.1128/aac.15.3.396
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Anti-Pseudomonas Activity of Azlocillin, Mezlocillin, and Ticarcillin

Abstract: The anti-pseudomonas activities of azlocillin and mnezlocilhin were compared with that of ticarcillin. We measured the minimal inhibitory and minimal bactericidal concentratiors of the three drugs against 20 different strains of Pseudomonas aeruginosa and found significantly lower values for azlocillin than for the other two drugs. We then infused 5 g of each drug into 10 volunteers on three consecutive days and determined the serum levels of the three antibiotics at 1-h intervals from 1 to 6 h after injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…However, similar problems existed in the prior study where carbenicillin plus sisomicin were administered at identical intervals. Second, some studies have reported significantly less bactericidal activity for azlocillin against P. aeruginosa compared with that of carbenicillin or ticarcillin (2,8); others have not (1,7). Our own studies demonstrated no differences in the rates of killing for P. aeruginosa by azlocillin or carbenicillin.…”
Section: Resultsmentioning
confidence: 52%
“…However, similar problems existed in the prior study where carbenicillin plus sisomicin were administered at identical intervals. Second, some studies have reported significantly less bactericidal activity for azlocillin against P. aeruginosa compared with that of carbenicillin or ticarcillin (2,8); others have not (1,7). Our own studies demonstrated no differences in the rates of killing for P. aeruginosa by azlocillin or carbenicillin.…”
Section: Resultsmentioning
confidence: 52%
“…aeruginosa. Azlocillin has been reported as being more active than ticarcillin (Coppens and Klastersky, 1979), although other findings suggest the converse (White, Comber and Sutherland, 1980). Cefsulodin has been shown to be more active than either azlocillin or ticarcillin (Zak et al, 1979).…”
Section: Introductionmentioning
confidence: 50%
“…In addition, the bactericidal activity of ureidopenicillins against P. aeruginosa has been reported to be much less than that of carbenicillin or ticarcillin (6,7,13,14), although in other studies little or no difference was observed in this respect between the two classes of penicillins (5,15,18).…”
mentioning
confidence: 91%